Acute suppurative thyroiditis with thyroid abscess in adults: clinical presentation, treatment and outcomes - Falhammar, Henrik (BMC Endocr Disord, 2019)
BACKGROUND: Abscess in the thyroid gland is a rare but severe infectious disease. The condition can have anatomic or iatrogenic underlying causes. If untreated it could be fatal. Pathogens vary considerably. Treatment is intravenous antibiotics, drainage, and sometimes surgery. METHODS: The electronic medical records of all adult patients with acute thyroiditis 2003–2017 treated at the Karolinska University Hospital (catchment area 2 million) in Sweden were systematically reviewed. RESULTS: Five patients were found in the catchment area. One patient from another region but known to us was also included. Thus, six patients (aged 28–73 years) were included in the study. Median length of hospital stay was 7.5 days (4–79 days). All were treated with antibiotics (intravenous n = 5, oral n = 1). Total antibiotic treatment duration was 13.5 days (10–41 days). Blood cultures were positive in three (streptococcus pneumonia, streptococci sanguineous, pepto streptococci), deep tissue culture in three (Escherichia coli, Candida, Hemophilic influenza) and no positive culture at all in two. Drainage was used in three patients. All patients recovered without recurrences. Surgery was performed twice in the acute phase in one. There was no recurrence during 7 years (3–12) of follow-up, but one patient died after three years (severe heart failure and pneumonia). CONCLUSION: Thyroid abscess in adults is extremely rare nowadays in the developed world. With prompt antibiotic therapy, drainage and in some cases thyroidectomy the prognosis seems favourable.